Determinan Nilai Perusahaan pada Perusahaan Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia - Raihan Taufiqurrahman; Siti Hidayati (IPB University, 2022)
This research is a quantitative research, the purpose of this research is to determine the effect of Capital Structure proxied by Debt to Equity Ratio (DER), Activities proxied by Working Capital Turnover (WCT), and Liquidity proxied by Current Ratio (CR) to Value Companies that are proxied by Price to Book Value (PBV). The population of this study are primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique uses probability sampling, with the slovin formula for the distribution of samples in each sub-sector, so that a sample of 53 companies is obtained and the research period is five years. Data analysis with the help of Microsoft Excel 2010 and hypothesis testing using Panel Data Regression Analysis with the help of the E-Views application version 12 and a significance level of 5 percent. The results of the study state that partially (1) Capital Structure has an effect on Firm Value, (2) Activities have no effect on Firm Value, (3) Liquidity has an effect on Firm Value.